ANTIFEBRILE THERAPY IN INFANTS - E.S. Keshishyan; G.Yu. Semina (Union of pediatricians of Russia, 2008)
The article demonstrates the necessity to prescribe the anti febrile medications to children on medical authority only. Besides, the authors stress that the doctor's tactics should be differential in the various types of fever. It is specifically essential for the pediatricians to take account both of the efficiency and safety of a prescribed medication, while choosing one.Key words: fever, fever types, antifebrile medications, children.